2015
DOI: 10.1161/circresaha.116.305178
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Triggers miR-143/145 Transfer From Smooth Muscle Cells to Endothelial Cells, Thereby Modulating Vessel Stabilization

Abstract: Rationale: The miR-143/145 cluster is highly expressed in smooth muscle cells (SMCs), where it regulates phenotypic switch and vascular homeostasis. Whether it plays a role in neighboring endothelial cells (ECs) is still unknown. Objective: To determine whether SMCs control EC functions through passage of miR-143 and miR-145. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 61 publications
5
146
0
Order By: Relevance
“…MiR-143 and miR-145 target hexokinase II (HKII) and integrin β 8 (ITGβ8) genes, respectively. 47 MiR-145 has been also implicated in the pathophysiology of atherosclerosis due to its effect on VSMC proliferation and phenotypic changes. In endothelial cells miR-143/145 expression is mediated by shear-responsive transcription factor -Kruppel like factor 2 (KLF2).…”
Section: Micrornas In Vascular Homeostasis and Diseasesmentioning
confidence: 99%
“…MiR-143 and miR-145 target hexokinase II (HKII) and integrin β 8 (ITGβ8) genes, respectively. 47 MiR-145 has been also implicated in the pathophysiology of atherosclerosis due to its effect on VSMC proliferation and phenotypic changes. In endothelial cells miR-143/145 expression is mediated by shear-responsive transcription factor -Kruppel like factor 2 (KLF2).…”
Section: Micrornas In Vascular Homeostasis and Diseasesmentioning
confidence: 99%
“…Notch signaling plays an important role during vascular development, and defects in this pathway may promote the development of PH (132,133). Interestingly, a recent study showed that miRNA in VSMCs may modulate the functions of EC through tunneling nanotubes formed between these two cell types (20). It clearly indicates the complexity of EC-VSMC communication.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence that the relationship between the EC and the SMC is not a simple one-way interaction from the endothelium to the SMC; rather, there are complicated interactions between them (9-11). Moreover, the communication patterns are not limited to paracrine signaling; cross-talk through myoendothelial gap junctions (MEJs), extracellular vesicles (EVs), and other mechanisms is critically involved (12)(13)(14)(15)(16)(17)(18)(19)(20). These mechanisms operate in a complicated but co-ordinated manner to maintain the homeostasis of the pulmonary circulation.…”
mentioning
confidence: 99%
“…70 In addition, recent evidences demonstrated the existence of a cross talk between ECs and SMCs mediated by these miRNAs. 32,92 In particular, it was hypothesized that miR-143/145 could be transferred by linelike membrane tubes which directly connect cells, 92 as well as through the secretion of extracellular vesicles. 32 As described earlier, miRNA-mediated cell-to-cell communication was also described for miR-126, which is enriched in apoptotic bodies derived from ECs, and provides an athero-protective effect.…”
Section: Endothelial Mirnas That Are Modulated After Injurymentioning
confidence: 99%
“…32 Additional reports demonstrated miR-143/145 transfer between ECs and VSMCs through different trafficking networks. 32,92 A specific cellto-cell communication network was described for miR-126 through EC-derived apoptotic bodies. 85 Also recently, it was reported that endothelial-derived microparticles can remotely modulate intercellular adhesion molecule 1 (ICAM-1) expression through intercellular transfer of miR-222.…”
Section: Cell-to-cell Cross Talkmentioning
confidence: 99%